2020
DOI: 10.21608/ebwhj.2019.17817.1038
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Laparoscopic Ovarian Drilling on Anti-Müllerian Hormone, LH/FSH ratio and inhibin B

Abstract: Background:Where laparoscopic ovarian surgery is to be recommended, there may be a small associated risk of lower ovarian reserve or loss of ovarian function. Based on its activities, Anti-Müllerian hormone (AMH) has been proposed to be involved in the pathophysiology of polycystic ovary syndrome (PCOS). AMH has become a useful clinical marker of ovarian reserve (OR) and reproductive disease in women. Its clinical utility has been expanding in scope for use in monitoring ovarian reserve, response to in vitro f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Anti-Mullerian hormone: While it is clear that there is a decrease in the ovarian reserve and volume following LOD, there is some discrepancy in the alterations in AMH concentrations. The average amount of AMH present in patients with PCOS was 8.57 ng/mL, which is significantly higher than in healthy controls in most studies [ 7 , 11 - 14 , 16 - 18 , 23 , 27 , 28 , 30 , 31 , 33 , 34 , 37 , 40 , 41 ]. Hendriks et al observed a significant and immediate decrease in AMH concentrations following LOD, whereas the majority of studies found it continued for six months with an average decrease of 36.92% [ 7 , 11 , 12 , 14 , 17 , 20 - 23 , 27 , 29 - 31 , 33 , 34 , 40 - 42 ].…”
Section: Reviewmentioning
confidence: 82%
See 2 more Smart Citations
“…Anti-Mullerian hormone: While it is clear that there is a decrease in the ovarian reserve and volume following LOD, there is some discrepancy in the alterations in AMH concentrations. The average amount of AMH present in patients with PCOS was 8.57 ng/mL, which is significantly higher than in healthy controls in most studies [ 7 , 11 - 14 , 16 - 18 , 23 , 27 , 28 , 30 , 31 , 33 , 34 , 37 , 40 , 41 ]. Hendriks et al observed a significant and immediate decrease in AMH concentrations following LOD, whereas the majority of studies found it continued for six months with an average decrease of 36.92% [ 7 , 11 , 12 , 14 , 17 , 20 - 23 , 27 , 29 - 31 , 33 , 34 , 40 - 42 ].…”
Section: Reviewmentioning
confidence: 82%
“…The average amount of AMH present in patients with PCOS was 8.57 ng/mL, which is significantly higher than in healthy controls in most studies [ 7 , 11 - 14 , 16 - 18 , 23 , 27 , 28 , 30 , 31 , 33 , 34 , 37 , 40 , 41 ]. Hendriks et al observed a significant and immediate decrease in AMH concentrations following LOD, whereas the majority of studies found it continued for six months with an average decrease of 36.92% [ 7 , 11 , 12 , 14 , 17 , 20 - 23 , 27 , 29 - 31 , 33 , 34 , 40 - 42 ]. Ogawa et al observed that when compared to preoperative AMH concentrations, there was a 0.55% change in overall AMH concentrations per puncture in all patients.…”
Section: Reviewmentioning
confidence: 82%
See 1 more Smart Citation
“…Laparoscopic ovarian drilling (LOD) appears useful in women with PCOS who do not respond to drug treatment and have no other reasons for infertility. This surgery method is a modified type of ovarian wedge resection (less invasive) during this process, the vascular stroma is destroyed (7). The purpose of this procedure is to increase follicular growth by reducing the amount of androgen and attenuating luteinizing hormone (LH) levels, and enhancing follicle-stimulating hormone (FSH) and sex hormone-binding globulin (4).…”
Section: Womenmentioning
confidence: 99%
“…The purpose of this procedure is to increase follicular growth by reducing the amount of androgen and attenuating luteinizing hormone (LH) levels, and enhancing follicle-stimulating hormone (FSH) and sex hormone-binding globulin (4). Both ovarian cauterization methods have been used through laparoscopy and carbon dioxide or neodymium-doped yttrium aluminum garnet lasers to create multiple holes in the ovarian and sternal surfaces (5,7).…”
Section: Womenmentioning
confidence: 99%